2007
DOI: 10.1074/jbc.m609920200
|View full text |Cite
|
Sign up to set email alerts
|

Activation Mechanism and Steady State Kinetics of Bruton's Tyrosine Kinase

Abstract: Bruton's tyrosine kinase (BTK) is a member of the Tec nonreceptor tyrosine kinase family that is involved in regulating B cell proliferation. To better understand the enzymatic mechanism of the Tec family of kinases, the kinetics of BTK substrate phosphorylation were characterized using a radioactive enzyme assay. We first examined whether autophosphorylation regulates BTK activity. Western blotting with a phosphospecific antibody revealed that BTK rapidly autophosphorylates at Tyr 551 within its activation lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 40 publications
6
52
1
Order By: Relevance
“…3C). The increased activity of the Itk_Btk loop-6 protein came entirely from an increase in k cat (a measure of catalytic rate); the value of k cat for the hyperactive Itk mutant was ~3.5- to 4-fold greater than that of wild-type Itk, and was the same as that of full-length Btk (15, 22). Thus, introduction of six activation segment residues of Btk into full-length Itk activated the mutant Itk similarly to full-length Btk by altering the catalytic rate of the Itk_Btk loop-6 protein, and not by increasing its affinity for its substrates.…”
Section: Resultsmentioning
confidence: 99%
“…3C). The increased activity of the Itk_Btk loop-6 protein came entirely from an increase in k cat (a measure of catalytic rate); the value of k cat for the hyperactive Itk mutant was ~3.5- to 4-fold greater than that of wild-type Itk, and was the same as that of full-length Btk (15, 22). Thus, introduction of six activation segment residues of Btk into full-length Itk activated the mutant Itk similarly to full-length Btk by altering the catalytic rate of the Itk_Btk loop-6 protein, and not by increasing its affinity for its substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Activity measurements are carried out by monitoring the phosphorylation levels of a peptide substrate in a radioactive assay or by detecting the level of autophosphorylation on the activation loop tyrosine (Y511 in Itk and Y551 in Btk) by western immunoblotting. While phosphorylation of the activation loop tyrosine is achieved by the activity of the Src family kinases Lck and Lyn respectively in vivo , under in vitro conditions Tec kinases autophosphorylate on the activation loop tyrosine[21; 22; 23]. …”
Section: Resultsmentioning
confidence: 99%
“…Activation of Tec kinases requires the phosphorylation of a conserved tyrosine within the activation loop[12; 21; 23]. Separate high-resolution structures of the Btk kinase domain with Y551 either phosphorylated (active) or unphosphorylated (inactive) have recently been reported[24].…”
Section: Resultsmentioning
confidence: 99%
“…Product formation was monitored as a function of time. Using a peptide substrate poly Glu-Tyr (poly EY), we observed a lag phase of ∼40-60 s in Btk product formation for the full-length enzyme (Figure 2A top panel), most likely the result of autophosphorylation on Y 551 (25). ESI-MS analysis indicated that the full-length enzyme was heterogeneously phosphorylated, ranging from 0 to 4 phosphate groups, with 0 and 1 phosphate as the most abundant species ( Figure 3A, top panel).…”
Section: Resultsmentioning
confidence: 99%